Students’ Mastery of Medical Vocabulary Learning Need at SMK Medika Pekalongan - Ani Mas Ayu; Ida Ayu Panuntun (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Medical vocabulary mastery is a fundamental component of English for Specific Purposes (ESP) instruction in vocational health education; however, the complexity of medical terminology, particularly terms derived from Latin and Greek, often creates substantial learning challenges for students. This study aimed to identify the difficulties experienced by eleventh-grade students at SMK Medika Pekalongan in mastering English medical vocabulary and to examine the factors contributing to these difficulties. A descriptive qualitative approach was employed, involving 36 students from the Medical Laboratory Technology program as respondents for the questionnaire and vocabulary test, while 10 students participated in semi-structured interviews. Data were collected through vocabulary tests, questionnaires, and interviews and were analyzed using qualitative data analysis procedures consisting of data reduction, data display, and conclusion drawing. The findings reveal that students faced multiple difficulties in mastering medical vocabulary, particularly in understanding the meanings of medical terms, memorizing vocabulary, pronouncing and spelling terms accurately, and comprehending texts containing extensive medical terminology. The vocabulary test results showed varied levels of mastery, with an average score of 67. Questionnaire findings indicated that most students perceived medical vocabulary as more difficult than general English vocabulary. The main factors contributing to these difficulties included insufficient practice, limited learning resources, unfamiliar Latin-based terminology, and inadequate instructional time. Interview data further indicated that students needed more interactive, contextualized, and practice-oriented learning methods to support better understanding and retention of medical terminology. The study concludes that medical vocabulary mastery remains a significant challenge for vocational health students and requires instructional approaches aligned with their specific vocational learning needs. These findings contribute to ESP instruction by emphasizing the importance of needs-based, contextualized, and practice-oriented strategies for improving medical vocabulary learning in vocational health education settings.